A novel method to improve the flotation separation of chalcopyrite from arsenopyrite under low-alkalinity conditions. (August 2022) - Luo, Yuanjia; Xia, Yuqin; Zhou, Hanyu; Yin, Chengzhe; Yang, Hao; Ou, Leming
Highlights: A novel method to improve the chalcopyrite/arsenopyrite flotation separation under low-alkalinity conditions is proposed. Separate use CTP can not achieve chalcopyrite/arsenopyrite flotation separation. Utilization of Ca 2+ as assistant depressant of CTP can well improve the flotation separation of chalcopyrite from arsenopyrite. Abstract: In this paper, we report a novel method to improve the flotation separation of chalcopyrite from arsenopyrite under low-alkalinity conditions. Single mineral flotation experiment results showed that individual use of CTP had weak inhibition on arsenopyrite flotation while no inhibition on chalcopyrite flotation. However, the addition of Ca 2+ greatly enhanced the inhibition of CTP on arsenopyrite flotation while slightly affected chalcopyrite flotation. The artificial mixed mineral flotation experiment results showed that a concentrate with Cu grade of 29.01% and As grade of 7.51% was obtained, with Cu recovery of 80.20% and separation efficiency of 41.75%. Compared with no addition of Ca 2+ and CTP, the Cu grade in the concentrate was increased by 10.53%, the As grade was decreased by 13.94%, and the separation efficiency was increased by 38.3%. This further demonstrated that utilization of Ca 2+ as an assistant depressant of CTP can well improve the flotation separation of chalcopyrite from arsenopyrite, which is consistent with the single mineral flotation experiment results. It is expected that this study will be helpful for the arsenic removal in the industrial production practice of arsenic-bearing copper sulfide ore.